2018
DOI: 10.5334/gjgl.449
|View full text |Cite
|
Sign up to set email alerts
|

Evidentials are syntax-sensitive: The view from Bangla

Abstract: This paper studies an evidential in Bangla which changes its evidential flavor based on its syntactic position. Forging novel connections with the literature on finiteness, indexical shift, and complementizer agreement, this paper demonstrates how evidentials can be sensitive to the presence of syntactic heads that represent the point-of-view of an utterance. Three main claims are made: (i) evidentials always take finite clauses which are perspective-sensitive, (ii) this perspective-sensitivity is syntactic, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…I locate it in a specifier of FinP. This is in accord with Bhadra 2018's proposal that there are null speaker and addressee coordinates in every finite clause. Secondly, I propose that the functional head that bears ɛ and agrees with the Hr DP is relatively low in the clause.…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…I locate it in a specifier of FinP. This is in accord with Bhadra 2018's proposal that there are null speaker and addressee coordinates in every finite clause. Secondly, I propose that the functional head that bears ɛ and agrees with the Hr DP is relatively low in the clause.…”
Section: Introductionsupporting
confidence: 75%
“…However, I propose that this locus of AA is relatively low in the clause in Magahi: in the FinP domain (in the cartographic structure of Rizzi 1997). This is in accord with Bhadra 2018: in her analysis of evidentials in Bangla, Bhadra proposes that there are null “speaker” and “addressee” coordinates in every finite clause. Furthermore, I claim that the functional head that agrees with the Hr DP is also relatively low in the clause: it is Fin, the head of FinP.…”
Section: The Proposalsupporting
confidence: 63%
See 2 more Smart Citations
“…However, this predicts obligatory matching between the features of embedded and matrix allocutivity, which is not borne out. In contrast, recent studies (Bhadra 2018;Alok 2020) have shown that there are null DP coordinates corresponding to 'speaker' and 'addressee' in every finite clause. If the above-mentioned representations of the addressee can be shown to host their own [status] feature, the facts in (i) can be explained.…”
Section: (85)mentioning
confidence: 86%